A Highly Efficient Photocatalytic System for Hydrogen Production by a Robust Hydrogenase Mimic in an Aqueous Solution - Wang, Feng; Wang, Wen-Guang; Wang, Xiao-Jun; Wang, Hong-Yan; Tung, Chen-Ho; Wu, Li-Zhu (Angewandte Chemie International Edition, 2011)
A robust, inexpensive, and efficient photocatalytic system consisting of an artificial water‐soluble [FeFe]‐H2ase mimic 1, CdTe quantum dots, and ascorbic acid (H2A), for H2 production in pure water at room temperature has been developed. With this system, 786 μmol (17.6 mL) H2 were obtained after 10 h irradiation (λ>400 nm) with TON up to 505 and TOF up to 50 h−1 under optimized conditions.